GLIM in diagnosing malnutrition and predicting outcome in ambulatory patients with head and neck cancer - Orell, Helena Kristiina; Pohju, Anne Katariina; Osterlund, Pia; Schwab, Ursula Sonja; Ravasco, Paula; Mäkitie, Antti (Frontiers in Nutrition, 2022)
Aim This study aimed to determine the prevalence of malnutrition in a head and neck cancer (HNC) population according to the Global Leadership Initiative on Malnutrition (GLIM) criteria and to assess its relation to survival. The secondary aim was to compare GLIM criteria to Patient–Generated Subjective Global Assessment (PG–SGA) and Nutritional Risk Screening 2002 (NRS 2002) methods. Methods The assessment was performed in a series of 65 curative patients with newly diagnosed HNC in a nutrition intervention study. Malnutrition was defined as PG-SGA classes BC and nutritional risk as NRS 2002 score ≥3 and was retrospectively diagnosed with GLIM criteria in prospectively collected data at diagnosis. Sensitivity, specificity, and kappa (κ) were analyzed. Predictive accuracy was assessed by calculating the area under curve (AUC) b y receiver operating characteristic (ROC) analysis. Kaplan–Meier and Cox regression analyses were used to evaluate association between malnutrition and overall survival (OS), and disease-free survival (DFS). Results GLIM-defined malnutrition was present in 37% (24/65) of patients. The GLIM showed 77% sensitivity and 84% specificity with agreement of κ = 0.60 and accuracy of AUC = 0.80 (p < 0.001) with PG-SGA and slightly higher sensitivity (83%) with NRS 2002 (κ = 0.58). Patients with GLIM-defined malnutrition had shorter OS (56 vs. 72 months, HR 2.26, 95% CI 1.07–4.77, p = 0.034) and DFS (37 vs. 66 months, HR 2.01, 95% CI 0.99–4.09, p = 0.054), than well-nourished patients. The adjusted HR was 2.53 (95% CI 1.14–5.47, p = 0.023) for OS and 2.10 (95% CI 0.98–4.48, p = 0.056) for DFS in patients with GLIM-defined malnutrition. Conclusion A substantial proportion of HNC patients were diagnosed with malnutrition according to the GLIM criteria and this showed a moderate agreement with NRS 2002- and PG–SGA-defined malnutrition. Even though the GLIM criteria had strong association with OS, its diagnostic value was poor. Therefore, the GLIM criteria seem potential for malnutrition diagnostics and outcome prediction in the HNC patient population. Furthermore, NRS 2002 score ≥3 indicates high nutritional risk in this patient group.